Serbian Traditional Music in the Lower Grades of Primary School: Teachers' Perspective - Маrija K. Tanasković; Danijela М. Sudzilovski (University of Belgrade, Teacher Education Faculty, 2023)
Traditional music should have greater significance and impact in education of children of younger school age. Curricular content of music education lessons enables students to learn about heritage and, therefore, learn to respect and cherish Serbian music and traditional music of other nations. Becoming familiar with traditional music in music lessons is one form of contributing to the development of the awareness of cultural and national treasure and of the need for its preservation and cultivation. The paper presents research that included 671 teachers from all districts of the Republic of Serbia. The aim of the research is to examine the opinions of teachers regarding the status of traditional music in the lower grades of primary school. The method of theoretical analysis and descriptive method were used. The results show that the contents of traditional music are practiced to a greater extent, but primary school teachers also believe that there is a need for including more of these contents in music lessons. When it comes to specifying which traditional contents are used in music lessons, it is noticeable that in different regions the contents related to the traditions of the local environment are nurtured. The respondents believe that students have positive reactions to traditional content but that it is not in the first place when it comes to children's interests. The research findings can serve as the basis for considering an improvement of continuous professional development courses for employees in education, but they can also be an incentive for collecting and publishing literature with the contents of traditional music in order to facilitate and improve the work of primary school teachers and the learning process of students.